E-entrepreneurship and ICT ventures : strategy, organization and technology - Kollmann, Tobias; Kuckertz, Andreas, 1972-; Stockmann, Christoph, 1980- (Hershey, PA : Business Science Reference, 2010)
'This book provides a unique overview of the current state of conceptual and empirical research at the interface of e-business and entrepreneurship'--Provided by publisher.
Includes bibliographical references (p. 335-372) and index.
Keywords: Electronic commerce; Entrepreneurship; Technological innovations -- Economic aspects